Potential mechanisms of acupuncture in enhancing cerebral perfusion of ischemic stroke - Wang, Lu; Su, Xin-Tong; Cao, Yan; Yang, Na-Na; Hao, Xiao-Wan; Li, Hong-Ping; Wang, Qing-Yong; Yang, Jing-Wen (Frontiers in Neurology, 2022)
Ischemic stroke is the predominant cause of long-term disability and death worldwide. It is attributable to the sudden interruption of regional cerebral blood flow, resulting in brain cell death and neurological impairment. Acupuncture is a widely used adjuvant treatment for ischemic stroke in China and shows promising efficacy in clinical practice. This review mainly focused on the evidence to illustrate several possible mechanisms of acupuncture therapy on cerebral perfusion in ischemic stroke. Studies have shown that acupuncture is probably effective in the enhancement of cerebral perfusion after ischemic stroke. It promotes the improvement of hemodynamics, the release of vasoactive substances, the formation of new blood vessels, as well as the restitution of microcirculation. Multiple factors may contribute to the variability in acupuncture's therapeutic effects, including the acupoint selection, stimulation frequency and intensity, and retaining needle time. Acupuncture has the potential to become a nonpharmacological adjuvant approach to enhance cerebral perfusion in ischemic stroke. Future studies are required to gain our insight into acupuncture as well as accelerate its clinical translation.